DEVELOPMENT OF LEGAL EMPLOYMENT DOCUMENTS PT. PETRO DAHANA READYMIX BASED ON PP NO. 35 YEAR 2021 CONCERNING PARTICULAR TIME WORKING AGREEMENTS - Alda Petronella Dahana Theysen; Windi Afdal (Universitas Internasional Batam, 2022)
Company legal documents, both financial documents and other documents have a very important position for the company. Company documents can be used as a reference for companies in making business decisions. Including documents regarding work agreements. Employment agreements between companies and employees have clearly become a big necessity. A work agreement is not just an oral agreement between individuals, but a work agreement must be legally written in writing and signed by both parties concerned. This is necessary to protect the rights and obligations of employees who work for a company. In February 2021 to be exact on the 16th, the government has issued 49 legal regulations no. 11 of 2020 concerning Job Creation (UU Ciptaker). The issued regulations consist of 45 Government Regulations (PP) and 4 Presidential Regulations (PERPRES). One of the PPs issued is PP No. 35 of 2021 concerning Specific Time Work Agreements, Outsourcing, Working Time, Work Relations and Rest Time and Termination of Employment (PP 35/2021). The Legal Contract summarizes part of the provisions of PP 35/2021 relating to a Specific Time Work Agreement (PKWT) and Outsourcing. Legal protection for workers, especially in the Specific Time Work Agreement (PKWT) is basically not running optimally, there are still many violations that often occur in a company due to the unclear rules regarding the implementation of a Specific Time Work Agreement (PKWT). This study aims to update the work agreement document based on changes to Law Number 13 of 2003 concerning Manpower and adjusted based on Government Regulation (PP) No. 35 of 2021.